Preparing Teachers: Highly Qualified to Do What? Editors’ introduction - Chin, Elaine; Wong, Pia L. (Education Policy Analysis Archives, 2013)
The No Child Left Behind Act of 2001 has had significant effects on teacher preparation programs, both in terms of changes required for policy compliance and through important program adjustments. These adjustments have largely been made in response to changes in partner schools and districts, where pacing guides, scripted curricula, benchmark testing and program improvement mandates are now the norm. In the context of anticipated robust policy activity in K-12 education and teacher education (e.g., possible re-authorization of the Elementary and Secondary Education Act, adoption of the Common Core Standards, new teacher certification performance assessments, etc.), it is important to understand the ways in which the current federal law, focused primarily on K-12 education, has also shaped teacher preparation programs. Paying attention to the dynamics involved in such context that his article introduces the articles of EPAA/AAPE’s Special Issue on Preparing Teachers: Highly Qualified to Do What?